Human filarial proteins attenuate chronic colitis in an experimental mouse model. (11th January 2018) - Togre, N.; Bhoj, P.; Goswami, K.; Tarnekar, A.; Patil, M.; Shende, M.
Summary: Encouraged by our earlier results of promising therapeutic effect of filarial recombinant proteins BmALT2, BmCys and WbL2 individually in the mouse model of acute ulcerative colitis, in this study, these proteins have been explored individually and in different combinations for their therapeutic potential in dextran sulphate sodium (DSS)‐induced chronic colitis mice. These mice, treated with filarial proteins, showed reduced disease parameters including body weight loss, disease activity index, macroscopic and histopathological scores of colon and myeloperoxidase activity in colonic mucosa. Among various treatment schemes, rBmALT2 + rBmCys which showed most pronounced therapeutic implication was found to downregulate the mRNA expressions of IFN‐γ and TNF‐α and upregulate IL‐10 and TGF‐β expression in the splenocytes. Also, increase in level of IgG1 and IgG2a isotypes in the sera of rBmALT2 + rBmCys‐treated colitis mice was noted. Activated NF‐κB level was found to be reduced in the colon of treated colitis mice compared to untreated one. In conclusion, filarial proteins in combination have been shown to improve the clinicopathologic status of chronic colitis through suppression of pro‐inflammatory immune response most possibly in NF‐κB‐dependent manner. We propose this therapeutic strategy to be tested further to be considered as an effective option in chronic colitis.